THEORETICAL STUDY OF THE CONDITIONS OF JOINT OPERATION OF OLD AND NEW CONCRETE - Viktorov, V. H.; Danilov, Ye. O.; Rieshetniak, T. P. (Science and Transport Progress, 2004)
An estimation of factors, influencing structural compatibility of old and new concretes, has been performed by authors of the paper. They have also attempted to make a review and select the instruments of finite element analysis, with the help of which it is possible to model the combined work of multi-layer concrete designs.